2021
DOI: 10.3390/ijerph18168890
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Trajectories and Factors in Koreans

Abstract: This study aimed to explore the drinking culture in Korea by sex, age, household type, occupation, and income level to identify demographic groups with prominent drinking behaviors and factors affecting their drinking. Furthermore, we evaluated recent changes, including those due to COVID-19, in drinking behavior, using data from the Korea Welfare Panel Study from 2010 to 2020. Panel analysis was performed to reveal the effects of material deprivation, depression, and sociodemographic factors on drinking behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Injunctive norms are perceptions regarding which specific drinking behaviors are socially acceptable [ 19 ]. The regression analysis revealed that injunctive norms were the second most important factor associated with the frequency and quantity of alcohol use for all age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Injunctive norms are perceptions regarding which specific drinking behaviors are socially acceptable [ 19 ]. The regression analysis revealed that injunctive norms were the second most important factor associated with the frequency and quantity of alcohol use for all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive norms refer to the perceptions of the drinking frequency and quantity of others. Injunctive norms refer to the perceived approval of drinking and represent perceived moral rules [ 18 , 19 ]. Injunctive norms and drinking motives could differ by a county’s drinking culture [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data on the age-related prevalence of current smoking and heavy drinking were similar to those previously reported. In general, the prevalence of current smoking and heavy drinking is considerably higher in young adulthood and decreases in elderly people [ 38 , 39 ]. Older individuals are more likely to participate in healthy lifestyle behaviors because of their higher probability of morbidity and mortality [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drinking is a social behavior influenced by various environmental factors such as availability, public policies, and acceptance of alcohol use. In Korea, drinking is characterized by a pattern of going back and forth between social drinking and problem drinking [ 7 ]. Owing to Korea’s remarkable economic growth that brought about widespread social changes, gender became an important variable affecting smoking patterns.…”
Section: Introductionmentioning
confidence: 99%